The Characterization and Hydrogen Production from Water Decomposition with Methanol in a Semi-Batch Type Reactor Using In, P-TiO2s - Joonwoo Kim; Hae-Ri Kim; Suk-Jin Choung (International Journal of Photoenergy)
The photocatalytic production of hydrogen from water using solar energy is potentially a clean and renewable source for hydrogen fuel. This study examines the production of hydrogen over In, P-TiO2s photocatalysts. 1 mol% In-TiO2 and P-TiO2 were produced using the solvothermal method and were treated at 500 and 800∘C to obtain anatase and rutile structure, respectively. The photocatalysts were characterized by X-ray diffraction, photoluminescence spectra, X-ray spectroscopy, UV-visible spectroscopy, and scanning electron microscopy. The production of H2 from methanol photodecomposition was greater over the rutile structure than over the anatase structure of TiO2. Moreover, the amount of hydrogen was enhanced over In-TiO2 and P-TiO2 compared to that over pure TiO2; the production increased by about 30%. The structural effect and the addition of In, P have significant influence on the H2 production from methanol/water decomposition.